Novel immunomodulatory effects of phytanic acid and its related substances in mice. (March 2016) - Nakanishi, Tomonori; Anraku, Mayuko; Suzuki, Ryoji; Kono, Tomoya; Erickson, Laurie; Kawahara, Satoshi
Highlights: Phytanic acid and its related substances inhibited IFN-γ production. Phytanic acid and phytol showed inhibitory activity on IL-17A production. Phytanic acid elicited immunomodulatory effects at its concentration in healthy humans. Abstract: Phytanic acid is one of the constituents of animal products with possible health benefits through improving lipid and glucose metabolism; however, its immunomodulatory effects remain undetermined. The in vitro effects of phytanic acid and its related substances on T-cell functions were investigated. Mouse splenocytes were stimulated by T-cell mitogens and incubated with phytanic acid, phytol, and pristanic acid followed by evaluation of cell proliferation and cytokine production. All phytanic acid-related substances significantly reduced IFN-γ, IL-4, and IL-10 production, with varying potencies, and had no significant effects on IL-2 production. Moreover, IL-17A production was inhibited by phytol and phytanic acid. Phytanic acid elicited immunomodulatory effects without inhibition of T-cell proliferation, and its effective concentration was less than 10 µM, which corresponds to the serum concentration of healthy humans. The present study suggests that phytanic acid has a potentially beneficial effect for amelioration of T-cell mediated autoimmune diseases.